ANALISIS PELAKSANAAN PENGAWASAN OLEH DINAS LINGKUNGAN HIDUP (DLH) KABUPATEN KUANTAN SINGINGI TAHUN 2019 (Studi Kasus Limbah PT. Wana Jingga Timur) - Yogi Aryo Logce; Auradian Marta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Pollution of palm oil industry waste that still occurs today is due to the person in charge of the business not managing the waste according to environmental quality standards, environmental management and environmental monitoring efforts (UKL-UPL). Based on the phenomena that occur, the formulation of this study is How is the Monitoring of the Environmental Service for Palm Oil Industry Waste and what factors hinder the implementation of this supervision. This study aims to find out how the supervision of the Environmental Service is carried out on palm oil industry waste and its management. This study uses qualitative methods with descriptive analysis research type. The data collection techniques are interviews, observation, and documentation. The key informants for this study were the Kuantan Singingi Regency Environmental Service in monitoring palm oil industrial waste and those in charge of the business. Based on the results of the research, it shows that the implementation of supervision has not been maximized and has not touched the entire existing palm oil industry. This can be seen from the violations of those in charge of business regarding waste management that does not comply with environmental quality standards, issues of environmental permits, phenomena of unresolved waste pollution, the adherence of those in charge of business in reporting Environmental Management Documents every semester. And the lack of strict sanctions given to palm oil industries that commit violations. as well as not yet effective supervision which is influenced by inhibiting factors such as monitoring support facilities, access and long distances. Keywords: Monitoring, Environment, Industrial waste